2018
DOI: 10.5897/ajcpath2018.0003
|View full text |Cite
|
Sign up to set email alerts
|

Histological and histochemical assessements on the effect of ethanol fruit extract of Phoenix dactylifera L. (Date Palm) on cerebral cortex of lead acetate treated wistar rats

Abstract: This study histologically and histochemically assess the effect of ethanol fruit extract of Phoenix dactylifera L. (EFPD) on the cerebral cortex of lead acetate exposed Wistar rats. Twenty rats were grouped into five groups (A to E, n=4). Group A (control) was administered distilled water (2 ml/kg), while groups B to E were treatment groups. Cerebral damage was induced in rats by the administration of lead acetate (120 mg/kg). Groups B, C, D and E were administered lead acetate (120 mg/kg) for a period of 3 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…In this study, the histological and histochemical analyses of the cerebral cortex from lead‐induced rats revealed marked cerebral damage with prominent alterations in the neuronal cells and necrosis, which resulted in a significant increase in the number of nonviable cells observed. Findings in this study are in agreements with the work of Sidhu and Nehru ( 2004 ), Mahmoud and Sayed ( 2016 ), and Lazarus et al ( 2018 ), who reported extensive histoarchitectural distortions on the cerebral cortex of mice and rats characterized by cellular shrinkages, vacuolations, neuronal cell damages, hyperchromatic cells, and pyknosis due to lead intoxication. Furthermore, the present study demonstrated multiple pathological lesions on the cerebellum of lead‐induced rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the histological and histochemical analyses of the cerebral cortex from lead‐induced rats revealed marked cerebral damage with prominent alterations in the neuronal cells and necrosis, which resulted in a significant increase in the number of nonviable cells observed. Findings in this study are in agreements with the work of Sidhu and Nehru ( 2004 ), Mahmoud and Sayed ( 2016 ), and Lazarus et al ( 2018 ), who reported extensive histoarchitectural distortions on the cerebral cortex of mice and rats characterized by cellular shrinkages, vacuolations, neuronal cell damages, hyperchromatic cells, and pyknosis due to lead intoxication. Furthermore, the present study demonstrated multiple pathological lesions on the cerebellum of lead‐induced rats.…”
Section: Discussionsupporting
confidence: 93%
“…Exposure to metals such as lead has been reported to be one of the leading causes of cerebral and cerebellar toxicity (Sidhu & Nehru, 2004 ). Cerebrum is the largest part of the brain responsible for superior brain functions such as motor movement, emotions, learning, and recognition, while the cerebellum is the major structure of the hindbrain responsible for motor coordination and balance (Lazarus et al, 2018 ; Mahmoud & Sayed, 2016 ). Both cerebellum and cerebrum are delicate structures that are vulnerable to intoxication resulting in a deficit of cognitive abilities and impaired motor coordination and balance (Bhattacharjee et al, 2018 ; Patrick, 2006b ).…”
Section: Introductionmentioning
confidence: 99%